In vitro antimicrobial activity and resistance mechanisms of the new generation tetracycline agents, eravacycline, omadacycline, and tigecycline against clinical Staphylococcus aureus isolates - Zeng, Weiliang; Zhang, Xiaotuan; Liu, Yan; Zhang, Yi; Xu, Mengxin; Wang, Sipei; Sun, Yao; Zhou, Tieli; Chen, Lijiang (Frontiers in Microbiology, 2022)
In this study, we investigated the in vitro activity and resistance mechanisms of the new generation tetracycline agents, namely eravacycline, omadacycline, and tigecycline, against Staphylococcus aureus isolates. A total of 1,017 non-duplicate S. aureus isolates were collected and subjected to susceptibility testing against eravacycline, omadacycline, and tigecycline using the broth microdilution method. Tetracyclines-resistant (eravacycline/omadacycline/tigecycline-resistant) isolates were selected to elucidate the resistance mechanisms using polymerase chain reaction (PCR), cloning experiment, efflux pump inhibition, and quantitative real-time PCR. The results of the antibacterial susceptibility testing showed that compared with omadacycline, eravacycline and tigecycline had superior antibacterial activity against S. aureus isolates. Among 1,017 S. aureus, 41 tetracyclines-resistant isolates were identified. These resistant isolates possessed at least one tetracycline resistance gene and genetic mutation in the MepRAB efflux pump and 30S ribosome units. A frameshift mutation in mepB was detected in most tetracyclines-resistant strains (except for JP3349) compared with tetracyclines-susceptible (eravacycline/omadacycline/tigecycline-susceptible) strains. This was first shown to decrease susceptibility to omadacycline, but not to eravacycline and tigecycline. After treatment with eravacycline, omadacycline or tigecycline, overexpression of mepA, tet38, tet(K) and tet(L) was detected. Moreover, multi-locus sequence typing showed a major clonal dissemination type, ST5, and its variant ST764 were seen in most tetracyclines-resistant strains. To conclude, eravacycline and tigecycline exhibited better activity against S. aureus including tetracycline-resistant isolates than omadacycline. The resistance to these new generation tetracyclines due to an accumulation of many resistance mechanisms.